Repeated 5-day cycles of low dose aldesleukin in amyotrophic lateral sclerosis (IMODALS): A phase 2a randomised, double-blind, placebo-controlled trial - Camu, William; Mickunas, Marius; Veyrune, Jean-Luc; Payan, Christine; Garlanda, Cecilia; Locati, Massimo; Juntas-Morales, Raul; Pageot, Nicolas; Malaspina, Andrea; Andreasson, Ulf; Kirby, Janine; Suehs, Carey; et al. (EBioMedicine, 2020)
Low-dose interleukin-2 (ld-IL-2) enhances regulatory T-cell (Treg) function in auto-inflammatory conditions. Neuroinflammation being a pathogenic feature of amyotrophic lateral sclerosis (ALS), we evaluated the pharmacodynamics and safety of ld-IL-2 in ALS subjects. We performed a single centre, parallel three-arm, randomised, double-blind, placebo-controlled study. Eligibility criteria included age < 75 years, disease duration < 5 years, riluzole treatment > 3 months, and a slow vital capacity ≥ 70% of normal. Patients were randomised (1:1:1) to aldesleukin 2 MIU, 1 MIU, or placebo once daily for 5 days every 4 weeks for 3 cycles. Primary outcome was change from baseline in Treg percentage of CD4+ T cells (%Tregs) following a first cycle. Secondary laboratory outcomes included: %Treg and Treg number following repeated cycles, and plasma CCL2 and neurofilament light chain protein (NFL) concentrations as surrogate markers of efficacy. Safety outcomes included motor-function (ALSFRS-R), slow vital capacity (SVC), and adverse event reports. This trial is registered with ClinicalTrials.gov, NCT02059759. All randomised patients (12 per group), recruited from October 2015 to December 2015, were alive at the end of follow-up and included in the intent-to-treat (ITT) analysis. No drug-related serious adverse event was observed. Non-serious adverse events occurred more frequently with the 1 and 2 MIU IL-2 doses compared to placebo, including injection site reactions and flu-like symptoms. Primary outcome analysis showed a significant increase (p < 0·0001) in %Tregs in the 2 MIU and 1 MIU arms (mean [SD]: 2 MIU: +6·2% [2·2]; 1 MIU: +3·9% [1·2]) as compared to placebo (mean [SD]: -0·49% [1·3]). Effect sizes (ES) were large in treated groups: 2 MIU ES=3·7 (IC95%: 2·3–4·9) and 1 MIU ES=3·5 (IC95%: 2·1–4·6). Secondary outcomes showed a significant increase in %Tregs following repeated cycles (p < 0·0001) as compared to placebo, and a dose-dependent decrease in plasma CCL2 (p = 0·0049). There were no significant differences amongst the three groups on plasma NFL levels. Ld-IL-2 is well tolerated and immunologically effective in subjects with ALS. These results warrant further investigation into their eventual therapeutic impact on slowing ALS disease progression. : The French Health Ministry (PHRC-I-14-056), EU H2020 (grant #633413), and the Association pour la Recherche sur la SLA (ARSLA).